2021
DOI: 10.1088/1757-899x/1045/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

A review on training and leadership development: its effectiveness for enhancing employee performance in Indian construction industry

Abstract: The second largest contributor to Indian GDP is the construction industry. It is the largest employing industry having huge economic potential which was valued over $126 billion in 2016 and it continues on a steady growth path. It is expected that the value of the real estate and construction market will increase seven-fold by 2028. Growth is likely to be underpinned by stable government support for infrastructure development, as well as through expanded private sector involvement. However, the industry suffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Internal career opportunities are pivotal in understanding an organization's commitment to its employees' growth and development. In the Indian corporate context, the nuances of these opportunities take unique shapes, especially when contrasting the practices of MNCs with those of DEs (Misra and Mohanty, 2021;Kostova and Zaheer, 1999). Budhwar and Khatri (2001) Simultaneously, MNCs are tailoring their practices to ensure cultural and regional relevance, leading to a richer, more holistic appraisal process.…”
Section: Ribs 344mentioning
confidence: 99%
“…Internal career opportunities are pivotal in understanding an organization's commitment to its employees' growth and development. In the Indian corporate context, the nuances of these opportunities take unique shapes, especially when contrasting the practices of MNCs with those of DEs (Misra and Mohanty, 2021;Kostova and Zaheer, 1999). Budhwar and Khatri (2001) Simultaneously, MNCs are tailoring their practices to ensure cultural and regional relevance, leading to a richer, more holistic appraisal process.…”
Section: Ribs 344mentioning
confidence: 99%
“…Trained and knowledgeable employees are a valuable asset to any organization, as they enhance effectiveness and efficiency in task performance. Attaining organizational goals is expected through positive behavioral changes resulting from learning experiences during training (Misra & Mohanty, 2021). Using various training methods, organizations seek to promote positive behavioral changes in their employees (Neck et al, 2017).…”
Section: Literature Review and Hypothesis Development Trainingmentioning
confidence: 99%
“…The research revealed motivation in the construction industry is determined by motivators, hygiene factors, extrinsic and intrinsic rewards, as well as some demographic factors like age and experience. A study conducted in the Indian construction industry showed a positive relationship between training and development of employees and their performance [29]. In South-East Nigeria, the relationship between psychological contracts and employee performance has been studied [30].…”
Section: Literature Reviewmentioning
confidence: 99%